SUBJECT-PERSONAL DETERMINANTS OF INNOVATIVE ACTIVITY OF SPECIALISTS OF COMPLEX TECHNICAL SYSTEMS - Vodopyanova , N.E.; Nikiforov , G. S.; Starchenkova, E. S.; Stolyarchuk , E. A. (Modern Psychology, 2019)
The development of complex technical systems (ITS) requires highly innovative activity of engineering personnel. The purpose of the study is to identify the subjectpersonal determinants of innovation activity and readiness for innovations of ITS specialists. The object of study: employees of design activities for the creation of military-industrial equipment in the amount of 50 people. As a result of empirical research, components of innovative readiness were analyzed, their interrelations with generalized innovative disposition, cognitive styles. The subject-personality determinants of innovative readiness were determined depending on the length of service in the field of designing the JTS. Results: predictors of innovative activity of ITS specialists are the following subject characteristics: high motivation for professional self-realization, responsibility for innovation, an increased degree of self-organization and the need for competence and autonomy of activity, high self-determination.
Keywords: innovation activity and readiness, subject-personal determinants, selforganization and self-determination